Antihypertensive drugs and glucose metabolism - Rizos, Christos V (Baishideng Publishing Group Inc, 2014)
Hypertension plays a major role in the development and progression of micro- and macrovascular disease. Moreover, increased blood pressure often coexists with additional cardiovascular risk factors such as insulin resistance. As a result the need for a comprehensive management of hypertensive patients is critical. However, the various antihypertensive drug categories have different effects on glucose metabolism. Indeed, angiotensin receptor blockers as well as angiotensin converting enzyme inhibitors have been associated with beneficial effects on glucose homeostasis. Calcium channel blockers (CCBs) have an overall neutral effect on glucose metabolism. However, some members of the CCBs class such as azelnidipine and manidipine have been shown to have advantageous effects on glucose homeostasis. On the other hand, diuretics and β-blockers have an overall disadvantageous effect on glucose metabolism. Of note, carvedilol as well as nebivolol seem to differentiate themselves from the rest of the β-blockers class, being more attractive options regarding their effect on glucose homeostasis. The adverse effects of some blood pressure lowering drugs on glucose metabolism may, to an extent, compromise their cardiovascular protective role. As a result the effects on glucose homeostasis of the various blood pressure lowering drugs should be taken into account when selecting an antihypertensive treatment, especially in patients which are at high risk for developing diabetes.